The Relationship Between Crude Oil Price and World Sector Indices - Kynnäs, Lauri (My University, 2019)
Crude oil affects almost all activities of our modern day society regardless of the shifting trend to green energy. Thus, it is still useful to understand its impact on world real output. Oil is such an important commodity that its price fluctuations either directly or indirectly affect all sectors of the world. This paper investigates the long-term relationship between crude oil price changes and world sector index returns using monthly MSCI ACWI sector index data from 1995 to 2018, which consists of almost hundred different sectors. The results are consistent with the previous literature. Most of the statistically significant oil coefficients (gammas) indicate negative sensitivity to oil price changes. However, majority of the oil related sectors gain positive gammas. Considering the results of this study, it can be stated that compared with other industries, oil related industries are expected to have long-term positive relationship with oil price changes. This could benefit e.g. global portfolio investors.
Keywords: Oil price sensitivity; Global industry sectors; Equity returns; Asset pricing; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|